2022
DOI: 10.3390/ani12070824
|View full text |Cite
|
Sign up to set email alerts
|

A Correlational Analysis of Phthalate Exposure and Thyroid Hormone Levels in Common Bottlenose Dolphins (Tursiops truncatus) from Sarasota Bay, Florida (2010–2019)

Abstract: Phthalates are chemical esters used to enhance desirable properties of plastics, personal care, and cleaning products. Phthalates have shown ubiquitous environmental contamination due to their abundant use and propensity to leach from products to which they are added. Following exposure, phthalates are rapidly metabolized and excreted through urine. Common bottlenose dolphins (Tursiops truncatus) sampled from Sarasota Bay, Florida, have demonstrated prevalent di(2-ethylhexyl) phthalate (DEHP) exposure indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…Our findings align with previous studies where DEP and DEHP are the most common compounds found in cetacean species, independent of the matrix or area of study [30,31,70]. Moreover, studies assessing PAE metabolite concentrations have also detected DEP and DEHP metabolites in different cetacean species [31][32][33][34]36,37,71,72].…”
Section: Occurrence Of Paes In Delphinidssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings align with previous studies where DEP and DEHP are the most common compounds found in cetacean species, independent of the matrix or area of study [30,31,70]. Moreover, studies assessing PAE metabolite concentrations have also detected DEP and DEHP metabolites in different cetacean species [31][32][33][34]36,37,71,72].…”
Section: Occurrence Of Paes In Delphinidssupporting
confidence: 91%
“…In the marine environment, marine mammals have been widely utilized as efficient indicators of environmental chemical pollution and its consequences due to their higher position in the food chain and long lifespan [27][28][29]. Prior research has found exposure to different phthalate compounds in varied cetacean species, including bottlenose dolphins (Tursiops truncatus [30][31][32][33][34][35][36][37]), killer whales (Orcinus orca [38]), sperm whales (Physeter macrocephalus [38]), long-finned pilot whales (Globicephala melas [38]), short-finned pilot whales (Globicephala macrorhynchus [30]), white-beaked dolphins (Lagenorhynchus albirostris [38]), harbour porpoises (Phocoena phocoena [38]), Risso's dolphins (Grampus griseus [30,31]), striped dolphins (Stenella coeruleoalba [30,31]), pygmy sperm whales (Kogia berviceps [30]), Fraser's dolphins (Lagenodelphis hosei [30]), and fin whales (Balaenoptera physalus [31]).…”
Section: Introductionmentioning
confidence: 99%